Digital transformation during a lockdown. (December 2020) - Fletcher, Gordon; Griffiths, Marie
Highlights: Limited studies exist on the use of VUCA as a lens for organisations to understand the impact of Covid-19. Overview of different stages of internal digital maturity that have presented businesses with different challenges during lockdown. Reflects on how the pandemic has revealed the fragility of digital immature organisations. Suggest new body of existing literature on crisis management in natural disasters that can be built upon to underpin current and future pandemics. Abstract: These are indeed exceptional and historic times, a global pandemic and public health emergency sitting side by side with heightened public awareness of the injustices of decades of institutional racism. This article considers the current pandemic and lockdown period through a VUCA lens and offers reflection on how the pandemic revealed the fragility of digitally immature organisations. VUCA, a managerial catchall acronym for Volatility, Uncertainty, Complexity and Ambiguity is a litmus test for recognising unpredictable external environments. We offer business leaders a caveat, it is dangerous to ignore the impact of VUCA on the smooth functioning of an organisation. In terms of digital transformation during lockdown this article offers three key lessons that can so far be discerned from the pandemic period, firstly organisations must improve their digital maturity, secondly, less digitally mature organisations are more fragile and finally organisations with higher levels of digital maturity are generally more flexible.